Context-Aware Communication and Computing: Applications for Smart Environment - Temdee, Punnarumol (Springer Series in Wireless Technology,, 2018)
This book introduces context-aware computing, providing definitions, categories, characteristics, and context awareness itself and discussing its applications with a particular focus on smart learning environments. It also examines the elements of a context-aware system, including acquisition, modelling, reasoning, and distribution of context. It also reviews applications of context-aware computing - both past and present - to offer readers the knowledge needed to critically analyse how context awareness can be put to use. It is particularly to those new to the subject area who are interested in learning how to develop context-aware computing-oriented applications, as well as postgraduates and researchers in computer engineering, communications engineering related areas of information technology (IT). Further it provides practical know-how for professionals working in IT support and technology, consultants and business decision-makers and those working in the medical, human, and social sciences.